Microsoft Office 2011 for Mac video quickstart - Schwartz, Steven A., 1951- (Peachpit Press, 2011)
"Visual QuickStart Guides are now even more visual: Building on the success of the top-selling Visual QuickStart Guide books, Peachpit now offers Video QuickStarts. As a companion to Microsoft Office 2011 for Macintosh: Visual QuickStart Guide, Peachpit offers more than an hour of short, task-based videos that will help you master Office 2011 for Mac top features and techniques; instead of just reading about how to use a tool, you can watch it in action. It's a great way to learn all the basics and some of the newer or more complex features of the program. This Video QuickStart guides you through the basics and new features of Word 2011 and Excel 2011. Veteran best-selling author and presenter Steve Schwartz provides in-depth instructions on many of the new features and changes introduced in Office 2011. Coverage of each application is jam-packed with information and tips that not only explain how to perform a task, but why you need this procedure and when it's best to use it."--Resource description page.